The mechanism of silicon on alleviating cadmium toxicity in plants: A review - Hou, Lei; Ji, Shengzhe; Zhang, Yao; Wu, Xiuzhe; Zhang, Li; Liu, Peng (Frontiers in Plant Science, 2023)
Cadmium is one of the highly toxic heavy metal elements, which has seriously threatened food safety and agricultural production in worldwide. Due to high solubility of cadmium, it can easily enter the plant, inhibit plant growth and reduce crop yield. Therefore, it is of great significance to find a way to alleviate the inhibitory effect of cadmium on plant growth. Silicon, the second-most abundant element in the Earth’s crust, has been widely reported to promote plant growth and alleviate cadmium toxicity. This review summarizes recent progress to elucidate the mechanism by which silicon mitigates cadmium toxicity in plants, including the reduction in cadmium uptake and transport, improvement in plant mineral nutrient supply, regulation of antioxidant systems and improvement in the physical structure of the plant body. Especially in this review, we summarized in detail and explain the role and mechanism of silicon maintaining water balance in enhancing plant resistance to cadmium. At the same time, we also conducted an in-depth analysis of the current research results to find out the current problems and suggested future research directions.